Perceptions and Realities for Distal Freehand Interlocking of Intramedullary Nails - Robert F. Ostrum (Advances in Orthopedics)
There is a perception that distal freehand interlocking (DFHI) of intramedullary nails can be difficult and time consuming. This study consists of a survey of surgeons’ practices for DFHI screws and their reasons for not using this technique. A survey was sent to 1400 orthopaedic surgeons who were asked to agree or disagree with statements regarding the difficulty and indications for the usage of distal freehand interlocking screws. The results were analyzed by practice demographics, resident availability, and completion of an orthopaedic trauma fellowship. Overall, 316 surgeons (22.6%) responded to the survey. Fellowship trained surgeons were 60% less likely to find DFHI difficult when compared to nonfellowship surgeons and surgeons with residents were 76% less likely to perceive DFHI as difficult than surgeons without residents. In all groups, 40–43% of surgeons used distal interlocking based on their comfort with the technique and not the fracture pattern. Distal freehand interlocking is perceived as difficult by community orthopaedic surgeons without residents and surgeons who have not done an orthopaedic trauma fellowship. Forty percent of surgeons based their usage of DFHI screws on their comfort with the technique and not the fracture pattern.